Makna Simbolik dalam Iklan Cerdas dan Target Perilaku Khalayak - Ferdinand Eskol Tiar Sirait (Universitas Medan Area, 2021)
This article aims to discuss the concept of smart advertising, especially with regard to the goals and effects of smart smart advertising to form the top of the mind of the audience. This research was conducted with library research (library research) with a descriptive analysis approach, namely collecting data, compiling or clarifying, and interpreting it. The technique used in this research, namely by analyzing advertisement sentences, seen from the use of interference. The data in this study were obtained from several sources in which there was interference. This study concludes that one of the most widely used strategies to increase the value of advertising is